PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) UNIVERSITAS RIAU - Dian Gusriani; Makhdalena Makhdalena; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of service quality on the satisfaction of cooperative members at the Indonesian Employee Cooperative (KPRI) University of Riau. The population in this study were all members of the Republic of Indonesia Employee Cooperative (KPRI) University of Riau totaling 854 members. Sampling in this study used the Slovin formula, based on calculations using the Slovin formula, with an error rate of 10%, 90 samples were obtained. Data collection techniques in this study using a questionnaire (questionnaire). The data analysis technique used is Descriptive Analysis, Classical Assumption Test and Hypothesis Testing. The results showed that service quality had a positive and significant influence on the satisfaction of members of the Indonesian Civil Servant Cooperative (KPRI) University of Riau.Key Words: Service Quality, Member Satisfaction